Safety and efficacy of calcium and magnesium infusions in the chemoprevention of oxaliplatin‐induced sensory neuropathy in gastrointestinal cancers. Issue 6 (25th April 2013) - Xu, Xi Tao; Dai, Zhang Han; Xu, Qi; Qiao, Yu Qi; Gu, Yan; Nie, Fang; Zhu, Ming Ming; Tong, Jin Lu; Ran, Zhi Hua
<x xml:space="preserve">Abstract</x> Objective To derive a more precise estimation on the safety and efficacy of calcium and magnesium (Ca and Mg) infusions in the prevention of oxaliplatin‐induced sensory neuropathy. Methods A total of 16 studies including 1765 individuals were involved in this meta‐analysis. Odds ratio (OR) and its 95% confidence interval (CI) were calculated. Results The difference in the incidence of oxaliplatin‐induced neuropathy grade ≥ 1 was statistically significant between the Ca and Mg infusions treatment group and the untreated group (National Cancer Institute common toxicity criteria [NCI CTC]: OR 0.44, 95% CI 0.31–0.62, P = 0.000; oxaliplatin‐specific scale [OSS]: OR 0.30, 95% CI 0.20–0.45, P = 0.000). Similar results were found in the incidences of oxaliplatin‐induced neuropathy grade ≥ 2 (NCI CTC: OR 0.60, 95% CI 0.46–0.77, P = 0.000; OSS: OR 0.45, 95% CI 0.30–0.67, P = 0.000). However, we did not detect a trend of fewer oxaliplatin‐induced neuropathy grade ≥ 3 incidences in the Ca and Mg infusions treatment group than the untreated group (NCI CTC: OR 0.67, 95% CI 0.44–1.01, P = 0.054; OSS: OR 0.66, 95% CI 0.34–1.29, P = 0.224). There was no difference in the response rate between the Ca and Mg treated group and the untreated group (OR 0.89, 95% CI 0.67–1.17, P = 0.391). Conclusion Ca and Mg infusions do not alter the efficacy of oxaliplatin‐based chemotherapy in gastrointestinal cancers, which may be reasonable to add them to lessen the incidence of neuropathy.